Evaluation of the FilmArray Meningitis/Encephalitis Molecular Panel in a Tertiary Care Public County Hospital. (4th October 2017) - Kim, Tae Hun; Minejima, Emi; Spellberg, Brad; Shulman, Ira; Holtom, Paul; Kang, Tarina; Butler-Wu, Susan M
Abstract: Background: Rapid diagnosis and treatment of meningitis and encephalitis is critical to reduce morbidity and mortality. The Biofire FilmArray Meningitis/Encephalitis (ME) Panel is a rapid, multiplex PCR assay that targets 14 common bacterial, viral, and fungal agents of ME. To our knowledge, there are no published studies evaluating the ME Panel's impact on clinical decision-making. Methods: Retrospective chart review was performed on 100 consecutive cases from January through April 2017 who underwent testing with the ME Panel. ME Panel results were compared with conventional testing methods. Each case was categorized as either contributory ( n = 51), possibly contributory ( n = 13), or noncontributory ( n = 36) based upon clinicians' acknowledgement and utilization of ME Panel results. Duration of ME antimicrobial therapy (bacterial, viral, and/or fungal) was determined for each case. Results: The average patient age was 41.1 years, with 37% of cases having either a new or established HIV diagnosis at the time of testing. The average turnaround time to reporting was 3.7 hours. The ME panel was positive in seven cases and demonstrated 100% sensitivity and 100% clinical specificity. During the study period, ME Panel detected infections with varicella-zoster virus, Cryptococcus neoformans in three different patients, Listeria monocytogenes, enterovirus, and Streptococcus pneumoniae . The ME panel detected L. monocytogenes and S. pneumoniae despite antibiotic therapy prior to lumbar puncture. The CSF cultures were subsequently negative but blood cultures were positive. Duration of antibacterial therapy was significantly decreased in the contributory and possibly contributory cases compared with noncontributory cases (28.38 hours vs. 76.69 hours, P = 0.04). Although not statistically significant, similar reductions were observed in duration of antiviral therapy ( P =  0.4). Conclusion: The FilmArray ME Panel demonstrated high sensitivity and specificity during the study period and was capable of detecting infections that would only have been diagnosed by blood culture. Duration of therapy was reduced in patients where the ME panel was contributory to clinical medical decision-making. Disclosures: S. M. Butler-Wu, Biofire Diagnostics: Consultant, Consulting fee and Research support